2019
DOI: 10.1126/sciadv.aav1887
|View full text |Cite
|
Sign up to set email alerts
|

Monsoon-driven Saharan dust variability over the past 240,000 years

Abstract: Saharan dust emissions over the past 240,000 years vary primarily with summer insolation rather than glacial-interglacial changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 104 publications
(109 citation statements)
references
References 73 publications
(98 reference statements)
8
87
0
1
Order By: Relevance
“…The specific details of this procedure may vary between laboratories, based on, for example, available instrumentation, sample throughput, and required precision. For example, the digestion usually includes a "cocktail" of nitric acid, hydrofluoric acid, and perchloric acid (e.g., Jacobel et al, 2017b), but some studies replace perchloric acid with hydrochloric acid and hydrogen peroxide (e.g., Skonieczny et al, 2019) and others omit any chlorinated acid altogether (e.g., Palchan & Torfstein, 2019). Some digestions are also assisted by pressurized microwave systems (e.g., Thöle et al, 2019).…”
Section: Analytical Methodologymentioning
confidence: 99%
“…The specific details of this procedure may vary between laboratories, based on, for example, available instrumentation, sample throughput, and required precision. For example, the digestion usually includes a "cocktail" of nitric acid, hydrofluoric acid, and perchloric acid (e.g., Jacobel et al, 2017b), but some studies replace perchloric acid with hydrochloric acid and hydrogen peroxide (e.g., Skonieczny et al, 2019) and others omit any chlorinated acid altogether (e.g., Palchan & Torfstein, 2019). Some digestions are also assisted by pressurized microwave systems (e.g., Thöle et al, 2019).…”
Section: Analytical Methodologymentioning
confidence: 99%
“…An important limitation on the precision of orbital tuning in the Mediterranean is, therefore, the incomplete understanding of the sub‐precessional relationship between sedimentation, climate, and insolation. Assuming increased North African dust flux to Mediterranean sediments during insolation minima (Larrasoaña et al, ; Skonieczny et al, ) extends back in time to at least the Tortonian (Rohling et al, ; Zhang et al, ) and that this process is the causal mechanism of the changes observed in our records as discussed in section , the use of seawater Pb isotopes has the potential to be particularly powerful. Based on modern observations (Marinou et al, ), dust is expected to have a widespread contribution across the entire Mediterranean region, affecting both the deeper, open Mediterranean, and the more restricted, marginal basins.…”
Section: Discussionmentioning
confidence: 80%
“…Observational data supporting this argument extend well into the Pliocene. Over the past 240 ka, deep Atlantic dust fluxes off the West African margin increase in parallel with decreases in insolation (Skonieczny et al, ). The study by Skonieczny et al () confirmed that orbital forcing, at the frequency of precession, is the dominant control on the timing of North African dust production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Climate variability in North Africa has been an important paleoclimate question involving African monsoon variability and vegetation-hydroclimate feedbacks and so forth (e.g., Harrison et al, 2014;Lézine et al, 2011). A large array of paleoclimatic records revealed that North Africa had experienced a remarkable humid period during the mid-Holocene (viz., the African humid period [AHP]) (e.g., Costa et al, 2014;deMenocal et al, 2000;Drake et al, 2011;Gasse, 2000;Lézine et al, 2011;McGee et al, 2013;Shanahan et al, 2015;Skonieczny et al, 2015Skonieczny et al, , 2019Tierney et al, 2011). The timing and magnitude of the rainfall changes related to the AHP were described by various historical and natural hydroclimate archives, mostly focused on the African monsoon evolution and vegetation hydroclimate feedbacks (Lézine et al, 2011).…”
Section: Introductionmentioning
confidence: 99%